Septuaginta-Psalm 90 in apotropäischer Verwendung: Vorüberlegungen für eine kritische Edition und (bisheriges) Datenmaterial - Kraus, Thomas J. (Biblische Notizen, 2005)
Psalm 90 of the Septuagint is very often preserved on papyri and epigraphic objects. In these contexts it mostly serves the purpose to protect from and / or against any evil powers. That is why the present study manifests a first attempt to depict systematically the popularity of this psalm and its apotropaeic usage. Thus, after some introductory remarks on the significance and application of Psalm 90 (91), the preliminary and up to now available material for a collective edition is to be presented.